Respuesta :
This a basic equation in which we have to attempt and solve for the value of 'x'. The basic thing to look out for this is we have to open the bracket (x - 1) by 100 i.e we are gonna to multiply (x - 1) by 100.
After simplification we do get,
[tex]\implies\rm{500 = 100(x - 1)}[/tex]
[tex]\implies\rm{500 = 100x - 100}[/tex]
[tex]\implies\rm{500 + 100 = 100x}[/tex]
[tex]\implies\rm{600 = 100x}[/tex]
[tex]\implies\rm{ \frac{600}{100} = x}[/tex]
[tex]\implies\rm{6 = x}[/tex]
[tex]\implies\rm{x = 6}[/tex]
- Thus the value of x is 6.
Answer:
6 = x (highly reccomend the explanation part)
Step-by-step explanation:
What you need to do is "open" the paranthesis. So 100(x-1) is basically
(* =times)
500 = 100 * x + 100 * -1
Let's simplify again
500 = 100x + (-100)
500 = 100x - 100
Now we need to isolate "x", so we add 100 to each side (to remove the -100)
600 = 100x
Simply divide everything by the "x" modifer (which is 100)
6 = x